2010
DOI: 10.21101/cejph.a3607
|View full text |Cite
|
Sign up to set email alerts
|

Food Intake, Leisure Time Activities and the Prevalence of Obesity among Schoolchildren in the Slovak Republic

Abstract: Aim of the study: In 2006-2008 a survey analyzing food patterns, intake of main food items and leisure time activities of 5,410 schoolchildren was carried out. Methods: The study was performed in 13 randomly selected regions of Slovakia. 5,410 elementary school children (2,848 girls and 2,562 boys) aged from 6.3 to 15.9 years, mean age was 11±2.6 years, were included. The data collected by questionnaire concerned nutrition and leisure time activities. Results: Noteworthy results are that only 63% of participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
4
7
0
4
Order By: Relevance
“…This fi nding contradicts with the fi ndings of the study done in Malaysia which revealed Television (73.3%) as a major source and school teachers (10%) as a least mentioned source of information regarding obesity 7. This study shows majority (77.5%) of adolescents were healthy weight, 10% were overweight and only 3.3% were obese. This fi nding is parallel with the fi ndings of one study which reported that 85.6% of children were healthy weight, almost 10% of them were overweight and only 4.5% children were obese 8 . This study is also consistent with another study conducted among higher secondary level adolescents with 5.8% overweight and 2.3% obese 9 .…”
Section: Discussionsupporting
confidence: 82%
“…This fi nding contradicts with the fi ndings of the study done in Malaysia which revealed Television (73.3%) as a major source and school teachers (10%) as a least mentioned source of information regarding obesity 7. This study shows majority (77.5%) of adolescents were healthy weight, 10% were overweight and only 3.3% were obese. This fi nding is parallel with the fi ndings of one study which reported that 85.6% of children were healthy weight, almost 10% of them were overweight and only 4.5% children were obese 8 . This study is also consistent with another study conducted among higher secondary level adolescents with 5.8% overweight and 2.3% obese 9 .…”
Section: Discussionsupporting
confidence: 82%
“…However, these results showed that the fruit consumption of Pakistani's adolescents is much lower than the New Zealand, US and European adolescents. [48][49][50] The dietary assessment results revealed that a large number of adolescents abstain from consuming healthy foods (such as fruits, vegetables, and meat and dairy products) which need interventions to promote healthy eating practices and lifestyles to prevent and reduce nutritional deficiencies and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Sedentary lifestyle is a pathogenic factor of obesity development and obesity-related cardiometabolic complications (8)(9)(10)(11)(12)(13)(14)(15). Increased physical activity and exercise training are well-established strategies for the treatment and prevention of obesity and its related diseases (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%